Давньоєгипетські пам’ятки в музейних зібраннях України (за дослідженнями українського єгиптолога Олени Романової) - Білик, Вікторія; Bilyk, Viktoriya (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті здійснено аналіз наукового доробку сучасного українського єгиптолога Олени Романової. Визначено, що до основних напрямів її наукових інтересів, крім політичної та соціальної історії Стародавнього Єгипту доби Давнього Царства, релігії й культури Стародавнього Єгипту, належать і пам’ятки Стародавнього Єгипту в музейних зібраннях України. Основну увагу зосереджено на публікаціях дослідниці стосовно аналізу колекції давньо-єгипетських пам’яток в Одеському археологічному музеї НАН України. An analysis of the scientific achievements of the modern Ukrainian Egyptologist Olena Romanova has been carried out. It is determined that the main directions of her scientific interests, in addition to the political and social history of Ancient Egypt of the Ancient kingdom, religion and culture of Ancient Egypt, include the monuments of Ancient Egypt in the museum collections of Ukraine. O. Romanov actively explores the collections of the Odessa Archaeological Museum, the National Kyiv-Pechersk Historical and Cultural Reserve, the National Museum of Arts named after Bogdan and Varvara Khanenkov. Thanks to her scientific researches, it has been clarified not only much information about certain Egyptian sights, but several artifacts have been found and attributed. Her scientific popularization activity is also very important, which makes information about Egyptian antiquities accessible to the general public and encourages visiting museums. The main focus of the article is concentrated on research publications devoted to the history of Egyptian research in Ukraine and the analysis of the collection of ancient Egyptian monuments in the Odessa Archaeological Museum of the National Academy of Sciences of Ukraine.
Ancient Egyptian Monuments in Museum Collections of Ukraine (for Researches of the Ukrainian Egyptologist ОІЄМ Romanova)
Keywords: єгиптологія; Стародавній Єгипет; давньоєгипетські пам’ятки; колекції; музейні зібрання України; Одеський археологічний музей; Egyptology; Ancient Egypt; ancient Egyptian monuments; collections; museum collections of Ukraine; Odessa Archaeological Museum